MODELISASI PIALA DENGAN PENGGABUNGAN HASIL DEFORMASI BENDA GEOMETRI RUANG - Putri, Nurika Heidianti; Kusno, Kusno; Juliyanto, Bagus (Majalah Ilmiah Matematika dan Statistika, 2018)
The cup is given to someone as a sign of apreciation and a gift of achievement. In general, the cup consists of the top, the middle, and the base. This research aims to obtain various forms of the design of cup that varied by merging the deformation results of solid geometry objects. This research method is divided into several stages. First, construct some basic objects as constituent components of cup from deformation of prism hexagon, tube, and cone. Second, set some basic objects of the component of cup on three types of modeling axis. Third, arrange program using software Maple 18. The results of this research obtained the procedure for designing various forms of constituent components of cup from the basic object of a prism hexagon, tube, and cone. Furthermore, the procedure for assembling the components of cup from the first procedure results on three types of modeling axis.